The Role of Ambidextrous Leadership in Employee Performance: A Literature Review on Manufacturing Industry - Ahmad Azmy; Denny Hartono (International Journal of Management, Accounting and Economics)
Employee performance becomes a strategic issue for companies facing the VUCA era (Volatility, Uncertainty, Complexity, and Ambiguity) following the subsiding of the Covid-19 pandemic.  During the Covid-19 pandemic, social distancing strategies were implemented, necessitating the discontinuation of gatherings in public areas. This led companies to change their work arrangements, such as adopting work-from-home practices. From the previous norm of employees working collectively and centrally in offices and business locations, there was a drastic shift to employees being dispersed and working from their respective homes. This research aims to investigate the implications of ambidextrous leadership on employee performance on manufacturing industry. The research process employed a literature review approach, conducted comprehensively. The research results suggest that ambidextrous leadership affects employee performance.  This study demonstrates that the type of ambidextrous leadership can enhance the likelihood of achieving business targets on manufacturing industry. This presents a challenge for future business development because the performance of employees working in the manufacturing industry sector greatly depends on a leadership style that can stimulate them through the innovation process.